(561) Management in Socialist Industry and Enterprises (Part I ) الإدارة في الصناعة والمؤسسات الاشتراكية- الجزء (1) - Linsel, Hermann; Sack, Kurt (INP, 2025)
The study addresses the fundamentals of socialist management in industry and enterprises, examining the economic position of public industrial enterprises and nationally-owned associations. It highlights key features of socialist management, such as directive-based governance and economic incentives, along with the challenges of centralized and decentralized decision-making. Various socialist management methods and their structural implementations within industrial enterprises and associations are analyzed. The study concludes by emphasizing the need to balance centralization and decentralization in decision-making to enhance industrial management efficiency and effectiveness. / /